Exploring Teluk Intan: a journey through tourism, food, & heritage / Dr. Suria Sulaiman - Sulaiman, Suria (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
Nestled in the heart of Perak, Malaysia, Teluk Intan is a charming town brimming with history, culture, and culinary delights. Growing up in Teluk Intan, many changes and progress can be seen from year to year. It is a city with various ethnic and religious backgrounds, and this is what makes Teluk Intan unique. Teluk Intan offers a unique blend of oldworld charm and modern attractions that make it a must-visit destination.